Pengaruh Nilai Tukar Dan Indeks Pasar Global Terhadap Indeks Harga Saham Gabungan Di Bursa Efek Indonesia - Rahmat Hardanil; Rini Sulistiyanti; Khadijah Darwin (LPPM STIEM BONGAYA, 2026)
This study aims to analyze the effect of exchange rates and global market indices on the Composite Stock Price Index (IHSG) on the Indonesia Stock Exchange for the 2020–2024 period. In the context of signaling theory, exchange rates and global market indices are considered macroeconomic signals that can influence investors' expectations and investment decisions. This study uses a quantitative approach with secondary data obtained from the official websites of Bank Indonesia, the Indonesia Stock Exchange (IDX), and Investing.com. The analytical method used is multiple linear regression with classical assumption testing, t-test, F-test, and coefficient of determination (R²). The results show that exchange rates and global market indices have a positive but not statistically significant effect on the IHSG. However, the positive direction of the relationship reflects the potential for relevant economic influences for investors. The coefficient of determination indicates that these two variables explain only 0.1% of the variation in the JCI, with the remainder influenced by other factors. This research provides implications for investors, monetary institutions, and academics to consider macroeconomic signals more closely in investment decision-making and financial analysis. Keywords: Exchange rate, Global Market Index, Composite Stock Price Index